Conductive particles, conductive materials, and connecting structures
Patent Information
- Application Number
- JP2022562536
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-16
- Filing Date
- 2021-12-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-15
AI Technical Summary
【0018】 本発明の実施例による導電粒子は、伝導層が多数の金属元素を含みながらも単層の構造を持つようにして伝導層から境界面がなくなりながらも、伝導層に結晶性を付与して結晶構造上の利点を介して優れた電気伝導度及び低抵抗効果を有し、硬度も増加する効果がある。
Smart Images

Figure 0007943814000004 
Figure 0007943814000005 
Figure 0007943814000006
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to conductive particles having a metal conductive layer on the surface of an insulating core, and more specifically, to conductive particles used as a core conductive material of an anisotropic conductive adhesive material for connecting fine-pitch circuits. The present invention also relates to a conductive material and a connection structure using the aforementioned conductive particles.
BACKGROUND ART
[0002] An anisotropic conductive material is a bonding material that transmits electrical signals between upper and lower electrodes and does not transmit electrical signals between left and right electrodes. The anisotropic conductive material is a bonding material mainly used for connecting a large number of electrodes to a driving IC, particularly in displays and the like.
[0003] Conductive particles are generally used in the form of a mixture and dispersion with a curing agent, an adhesive, a resin binder, and other additives in anisotropic conductive materials, such as Anisotropic Conductive Film, Anisotropic Conductive Adhesive, Anisotropic Conductive Paste, Anisotropic Conductive Ink, Anisotropic Conductive Sheet, and the like.
[0004] The anisotropic conductive material is used in FOG (Film on Glass; flexible substrate-glass substrate), COF (Chip on Film; semiconductor chip-flexible substrate), COG (Chip on Glass; semiconductor chip-glass substrate), FOB (Film on Board; flexible substrate-glass epoxy substrate), and the like.
[0005] For example, assuming the bonding of a semiconductor chip and a flexible substrate, anisotropic conductive materials can be used to create a connection structure in which conductive particles electrically connect the electrodes of the substrate and the electrodes of the semiconductor chip. This can be achieved by placing the anisotropic conductive material on the flexible substrate, stacking the semiconductor chips, and curing the anisotropic conductive material under pressure / heat.
[0006] When the conductive particles are used in the anisotropic conductive material, they are mixed with additives such as curing agents, adhesives, resin binders, and fillers, and when they become a connecting structure after pressurization / heating, the electrical connection between the upper and lower electrodes is maintained by the curing / adhesion of the anisotropic conductive material.
[0007] However, conventional conductive particles with a metallic conductive layer on the surface of an insulating core have multiple conductive layers to improve the conductivity of the conductive layer. In this case, some parts are formed amorphously, or boundaries exist between each layer of the conductive layer, resulting in an increase in resistance at the boundaries. This increases the connection resistance of anisotropic conductive materials using conductive particles, which in turn increases reliability resistance. [Overview of the project] [Problems that the invention aims to solve]
[0008] The technical problem that the embodiments of the present invention aim to solve is to provide conductive particles having a single conductive layer while possessing high strength, low initial connection resistance and resistance increase rate, an anisotropic conductive material containing the same, and an anisotropic connection structure, in order to solve the problems of the prior art described above. [Means for solving the problem]
[0009] One aspect of the present invention is a conductive particle, Insulating core and The insulating core includes a conductive layer containing at least two elements, The diffraction pattern obtained by analyzing the conductive layer using XRD shows that at least two diffraction circles are formed, and the average length of the major axis of the crystal grains in the conductive layer is 8 nm to 13 nm.
[0010] The conductive layer preferably comprises Ni and at least one element selected from the group consisting of B, P, N, Pd, Pt, W, Au, Ag, Mo, and Co, and the radius of the innermost diffraction circle among the diffraction circles is preferably 4.93 (l / nm) ± 0.2 (l / nm).
[0011] When the conductive layer is divided into a first region adjacent to the insulating core, a second region adjacent to the first region, and a third region adjacent to the second region and located on the outermost side, it is preferable that the conductive layer is a single layer with no interlayer boundaries between the first, second, and third regions.
[0012] Preferably, the elemental content of the conductive layer varies depending on the region.
[0013] The conductive layer preferably contains at least two elements selected from the group consisting of B, P, N, Pd, Pt, W, Au, Ag, Mo, and Co.
[0014] In this case, the conductive particles may further include protrusions on the surface of the conductive layer, and may further include an insulating layer or insulating particles on the surface of the conductive layer, and it is preferable that the outermost layer on the conductive layer is treated with a hydrophobic rust inhibitor for rust prevention.
[0015] Another aspect of the present invention provides an anisotropic conductive material comprising at least one of the conductive particles.
[0016] Another aspect of the present invention provides a connecting structure comprising at least one of the conductive particles.
[0017] Another aspect of the present invention provides an electronic device comprising at least one of the conductive particles. [Effects of the Invention]
[0018] The conductive particles according to the embodiment of the present invention have a single-layer structure in which the conductive layer contains numerous metal elements, eliminating the interface from the conductive layer. Furthermore, crystallinity is imparted to the conductive layer, resulting in excellent electrical conductivity and low resistance through the advantages of the crystal structure, and also increasing hardness.
[0019] Therefore, by using conductive particles according to the embodiments of the present invention, it is possible to provide an anisotropic conductive material and an anisotropic connection structure that not only have a low initial connection resistance value but also exhibit a low resistance increase even after high-temperature / high-humidity reliability testing, while maintaining a low resistance increase. [Brief explanation of the drawing]
[0020] [Figure 1] This is a 500,000x magnification image of the conductive layer of conductive particles according to an embodiment of the present invention, taken using a field emission transmission electron microscope (FETEM-JEM-2100F, 200kV). [Figure 2] This is a diffraction pattern of the conductive layer of conductive particles according to an embodiment of the present invention, measured using XRD (X-RAY DIFFRACTOMETER, product name: SmartLab, manufacturer: Rigaku Corporation, target: Cu, electromagnetic wave used: Kα). [Figure 3] This diagram shows a method for determining the radius of the diffraction circle. [Figure 4] This figure shows the position of the conductive layer of conductive particles according to one embodiment of the present invention. [Modes for carrying out the invention]
[0021] Before describing the present invention in detail below, it should be understood that the terms used herein are for the purpose of describing specific embodiments and are not intended to limit the scope of the invention, which is limited solely by the appended claims. All technical and scientific terms used herein have the same meaning as commonly understood by those of the ordinary art, unless otherwise noted.
[0022] Throughout this specification and the claims, unless otherwise stated, the term "comprise, comprises, comprising" means including the referenced objects, steps, groups of objects, and groups of steps, and is not used in the sense of excluding any other objects, steps, groups of objects or groups of steps.
[0023] On the other hand, various embodiments of the present invention may be combined with any other embodiments unless clearly indicated to the contrary. Any feature indicated as being particularly preferred or advantageous may be combined with any other feature indicated as being preferred or advantageous.
[0024] The conductive particles according to the embodiments of the present invention are conductive particles contained between electrodes to electrically connect the electrodes, and the electrodes use oxide electrodes such as ITO (indium tin oxide) and ZnO (zinc oxide), metal electrodes made of metal, and metal powder. For example, it can be provided as a paste electrode or the like, in which a paste is prepared by mixing Ag or Cu powder and a resin, and the electrode is formed from the paste. The electrode may include at least one of the oxide electrode, the metal electrode, and the paste electrode.
[0025] The conductive particles according to the embodiments of the present invention include insulating core particles and a conductive layer provided on the surface of the insulating core particles, and may have protrusions of a conductive material that is the same as or different from the conductive layer on the surface.
[0026] The insulating core particles according to the embodiments of the present invention are not particularly limited. For example, resin fine particles or organic / inorganic hybrid particles can be used.
[0027] Resin fine particles are copolymers obtained by polymerizing monomers such as urethane, styrene, acrylate, benzene, epoxy, amine, and imide monomers, or modified monomers thereof, or mixed monomers thereof, using methods such as seed polymerization, dispersion polymerization, suspension polymerization, and emulsion polymerization.
[0028] When organic / inorganic hybrid particles have a core-shell structure, the shell is inorganic when the core is organic, and the shell is organic when the core is inorganic. For organic materials, the above monomers, modified monomers, or mixed monomers can be used. For inorganic materials, oxides such as SiO2, TiO2, Al2O3, ZrO2, etc., nitrides such as AlN, Si3N4, TiN, BaN, etc., and carbides such as WC, TiC, SiC can be used. Methods for forming the shell include chemical coating, Sol-Gel method, Spray Coating, CVD (chemical vapor deposition), PVD (physical vapor deposition), and plating. Furthermore, a form in which inorganic particles are dispersed within an organic matrix is also possible, as is a form in which organic particles are dispersed within an inorganic matrix, and a form in which organic / inorganic particles are dispersed in a 50:50 ratio.
[0029] The conductive layer of conductive particles according to the embodiment of the present invention is a conductive layer containing at least two elements. In this case, the conductive layer contains at least two elements selected from the group consisting of B, P, N, Ni, Pd, Pt, W, Au, Ag, Mo, and Co.
[0030] Preferably, the material contains nickel and at least one element selected from the group consisting of B, P, N, Pd, Pt, W, Au, Ag, Mo, and Co.
[0031] For example, it can be composed of two-metal alloys such as nickel-phosphorus, nickel-boron, nickel-tungsten, and nickel-nitrogen, or three-metal alloys such as nickel-phosphorus-tungsten, nickel-boron-tungsten, nickel-phosphorus-cobalt, nickel-phosphorus-palladium, and nickel-boron-palladium. It can also be composed of four-metal alloys such as nickel-phosphorus-boron-tungsten, nickel-phosphorus-palladium-tungsten, and nickel-boron-tungsten-platinum. In addition, it can be composed of alloys of five or more metals.
[0032] As illustrated, nickel is essential because it has good electrical conductivity, and since the insulating core used in conductive particles mainly consists of polymer beads, it has excellent adhesion to plastics.
[0033] The conductive layer in this embodiment is a single layer without interlayer boundaries, and the elemental content within the conductive layer can vary depending on the region within the conductive layer, but it is manufactured to be polycrystalline throughout the entire region. Manufacturing the conductive layer as polycrystalline with small grain boundaries is advantageous in terms of electrical conductivity.
[0034] Therefore, the conductive layer of conductive particles according to one embodiment of the present invention is a single-layer polycrystalline layer without interlayer boundaries, containing two or more elements and having fine crystal grains with an average major axis length of 8 to 13 nm.
[0035] In this case, when the diffraction pattern of the entire region of the conductive layer was measured using XRD, it was preferable that multiple diffraction circles were formed, and the radius of the innermost diffraction circle was 4.93 ± 0.2 (l / nm). On the other hand, when measuring the XRD diffraction pattern, the radius of the diffraction circle was measured in the reciprocal grid, and for convenience, the unit l / nm was used.
[0036] The size of the crystal grains and the length of the radius of the innermost diffraction circle, as described above, are determined by the type and content of the elements used, the reaction rate, etc. Therefore, because the elements contained within and their content differ depending on the region of the conductive layer of the present invention, the radius of the innermost diffraction circle changes in each region of the conductive layer, based on the size of the crystal grains and the measurement of the diffraction pattern across the entire region of the conductive layer using XRD.
[0037] In this invention, the conductive layer has crystal grains with an average major axis length of 8 to 13 nm throughout the entire region of the conductive layer, regardless of the variation in content depending on the region, and the radius of the innermost diffraction circle in the XRD analysis diffraction pattern is kept within 4.93 (l / nm) ± 0.2 (l / nm). This is because it is possible to form a single layer with high adhesion to the insulating core and without forming interlayer boundaries within the conductive layer.
[0038] For example, the conductive layer can be divided into three regions based on its composition: a first region adjacent to the insulating core, a second region adjacent to the first region, and a third region located on the outermost side adjacent to the second region. Furthermore, the conductive layer can be divided into three regions based on its composition: a fourth region formed with a first composition, a fifth region formed with a second composition, and a sixth region formed with a third composition.
[0039] In this case, the conductive layer according to the embodiment of the present invention satisfies the range of the aforementioned average length along the major axis and the radius of the innermost diffraction circle in all of the first, second, and third regions, as well as the fourth, fifth, and sixth regions.
[0040] The fact that the conductive layer in the embodiment of the present invention is crystalline with the aforementioned grain boundaries was confirmed by the FETEM image of the conductive layer of conductive particles in one embodiment of the present invention shown in Figure 1, taken at a magnification of 500,000, and by the diffraction pattern obtained by XRD analysis of the conductive layer shown in Figure 2, which confirmed that it is a polycrystalline conductive layer.
[0041] As shown in Figure 1, a polycrystalline conductive layer is confirmed because grain boundaries with different crystal orientations are observed. Furthermore, the size of the conductive grains is confirmed to be 5.13 to 12.76 nm relative to the long axis, with an average of approximately 9.76 nm.
[0042] Furthermore, Figure 2 shows multiple diffraction circles, allowing for confirmation of crystallinity. In this case, the radius of the innermost diffraction circle falls within the range mentioned above.
[0043] On the other hand, a polycrystalline conductive layer having a single layer containing two or more elements and no interlayer interfaces, yet with small grain boundaries, according to an embodiment of the present invention, is not limited to this method but can be achieved by electroless plating in which the element content and reaction rate within the plating layer are controlled.
[0044] For example, electroless nickel plating can form conductive layers using sodium hypophosphite for Ni-P plating, sodium borohydride (SHB), dimethylamine borane (DMAB), diethylamine borane (DEAB), etc., depending on the type of reducing agent used. It can also form conductive layers using hydrazine for Ni-N plating. Furthermore, by adding metal salts containing Pd, Pt, W, Au, Ag, Mo, Co, etc., electroless alloy plating such as Ni-PW, Ni-BW, Ni-P-Co-W, Ni-B-Co-W, Ni-W, Ni-Co, Ni-Pd, and Ni-P-Pd is possible.
[0045] In the case of electroless plating with Ni-P as the main component, if the P content is high, an amorphous layer is formed, which has excellent corrosion resistance, but it has the problem of low strength and high resistance in terms of electrical conductivity (10 μΩcm @ 20℃ for P and 6.97 μΩcm @ 20℃ for Ni). Therefore, keeping the P content below 3% is advantageous for the formation of crystalline material.
[0046] Furthermore, in the case of electroless plating with Ni-B as the main component, the resistivity of B (1.5 × 10^12 μΩcm @ 20℃) is very high, so even if B is present in a content of a few percent, an amorphous plating layer will be formed. Therefore, keeping the B content below 0.5% is advantageous for the formation of crystalline material.
[0047] In the case of electroless plating with Ni-N as the main component, the corrosion resistance is inferior to that of Ni-P and Ni-B, but if the N content is 2% or less, a conductive layer can be formed in a crystalline state.
[0048] On the other hand, while conductive layers consisting of Ni-P, Ni-B, and Ni-N as described above may be used, if strength or corrosion resistance is particularly required, or to ensure other physical properties, elements such as Pd, Pt, W, Au, Ag, Mo, and Co may be further included, and a single crystalline plating layer can be formed using an alloy electroless plating method.
[0049] In order to form a polycrystalline material with no interlayer boundaries and small grain size, it is necessary to control the reaction rate as well as the elemental content. The reaction rate is adjusted using the amount of reducing agent, the temperature of the plating solution, and the pH.
[0050] If the reaction rate is slow, a conductive layer is formed in the amorphous region. If the reaction rate is too fast, the balance of the plating solution is disrupted, making the plating unreliable or resulting in defective plating that makes commercialization impossible.
[0051] The shape of the protrusions of the conductive particles of the present invention is not particularly limited. Spherical, needle-shaped, polygonal shapes are also possible. The size of the protrusions of the present invention is not particularly limited. Preferred protrusions are convex shapes with a size of 50 nm to 500 nm, and even more preferred protrusions have a size of 100 to 300 nm.
[0052] The method for forming protrusions on conductive particles according to the present invention is not particularly limited. For example, a catalytic substance can be applied to the surface of insulating core particles, and a conductive layer and protrusions can be formed via electroless plating. Alternatively, small metal or inorganic particles can be attached to insulating core particles, and a conductive layer and protrusions can be formed by electroless plating.
[0053] In this invention, it is preferable that the outermost layer of the conductive particles has an insulating layer. As electronic products become smaller and more integrated, the electrode pitch becomes smaller, and if there are no insulating particles on the outermost layer, a phenomenon of electrical current flow with adjacent electrodes occurs. Methods for forming an insulating layer include chemically attaching insulating particles to the outermost layer of conductive particles using functional groups, dissolving an insulating solution in a solvent and then coating by spraying or deposition, and attaching insulating particles to the outermost layer of conductive particles and then coating by applying hot air and impact.
[0054] It is preferable to apply a rust-preventive treatment to the conductive particle conduction layer of the present invention. This is because rust-preventive treatment increases the contact angle with water, improving reliability in high-humidity environments, and reduces the deterioration of the performance of connecting members by allowing impurities to dissolve in water. Therefore, rust inhibitors that are generally hydrophobic are used. For coating, methods such as deposition or spraying can be used after dissolving the rust inhibitor in a solvent.
[0055] An anisotropic conductive material can be manufactured by dispersing the conductive particles of the present invention in a binder resin. Examples of anisotropic conductive materials include anisotropic conductive paste, anisotropic conductive film, and anisotropic conductive sheet.
[0056] The resin binder is not particularly limited. Examples include vinyl resins such as styrene-based, acrylic-based, and vinyl acetate-based resins; thermoplastic resins such as polyolefin-based and polyamide-based resins; and curable resins such as urethane-based and epoxy-based resins. The above resins can be used individually or in combination of two or more. Radical initiators such as BPO (Benzoyl Peroxide), photoinitiators such as TPO (Trimethylbenzoyl Phenylphosphinate), and epoxy latent curing agents such as HX3941HP can be used individually or in combination with the resin for the purpose of polymerization or curing. In addition, other substances can be added to the anisotropic conductive material binder resin, as long as they do not hinder the achievement of the objectives of the present invention. Examples include colorants, softeners, heat stabilizers, light stabilizers, antioxidants, and inorganic particles.
[0057] The method for manufacturing the anisotropic conductive material described above is not particularly limited. For example, conductive particles can be uniformly dispersed in a resin binder to be used as an anisotropic conductive paste, or a thin layer can be applied to release paper to be used as an anisotropic film.
[0058] The connection structure of the present invention connects circuit boards using conductive particles with an insulating core of the present invention or an anisotropic conductive material of the present invention. For example, it can be used as a method for connecting a smartphone display semiconductor chip to a glass substrate that forms a circuit, or for connecting μ-LEDs, mini-LEDs, and circuit boards. [Examples]
[0059] 1) Synthesis of insulating core particles 1100g of monomer TMMT (Tetramethylol Methane Tetaacrylate), 400g of DVB, 15g of HDDA, and 30g of Styrene were placed in a 3L glass beaker, 5g of initiator BPO was added, and the mixture was treated in a 40kHz ultrasonic bath for 10 minutes to prepare the first solution. 3,000g of deionized water was placed in a 5L PP beaker, and 500g of the dispersion stabilizer PVP (Polyvinylpyrrolidone)-30K and 200g of the surfactant Solusol (Dioctyl sulfosuccinate sodium salt) were added to it, then dissolved to prepare the second solution. The first and second solutions were placed in a 50 L reactor, 40,000 g of deionized water was added, and the mixture was treated with an ultrasonic homogenizer (20 kHz, 600 W) for 90 minutes. The solution was heated to 35°C while rotating it at 120 rpm, maintained at that temperature for 3 hours, and then heated again to 85°C. After the solution reached 85°C, it was maintained at that temperature for 16 hours to carry out the polymerization process. Polymerized fine particles were subjected to filtration, washing, classification, and drying processes to obtain core resin fine particles. The average diameter of the manufactured core resin fine particles was measured using a Particle Size Analyzer (BECKMAN MULTISIZER TM3) and the mode value was used. The number of core fine particles measured was 75,000. The average diameter was 3.51 μm.
[0060] 2) Formation of an insulating core particle outer shell conductive layer (1) Catalyst treatment process 30 g of the manufactured insulating core particles were placed in a solution of 800 g of deionized water, 0.5 g of the surfactant Triton X100, and 10 g of sulfuric acid, and treated in an ultrasonic bath for 1 hour to perform a washing and degreasing process to remove excess unreacted monomers and oil components present in the insulating core particles. The final step of the washing and degreasing process was a three-times rinse using deionized water at 45°C. The insulating core particles, which had undergone the degreasing and washing steps described above, were placed in a solution prepared by dissolving 150 g of stannous chloride and 300 g of 35-37% hydrochloric acid in 600 g of deionized water. Sensitization treatment was performed by deposition and stirring at 30°C for 30 minutes, followed by three washes with water. Sensitized insulating cores were placed in a mixture of 1 g of palladium chloride, 200 g of 35-37% hydrochloric acid, and 600 g of deionized water, and activated at 40°C for 1 hour. Ultrasound was applied using an ultrasonic bath during the activation process. After the activation process, the cores were rinsed with water three times. The activated insulating core was placed in a solution of 100 g of 35-37% hydrochloric acid and 600 g of deionized water, and accelerated by stirring at room temperature for 10 minutes. After the accelerated treatment, the core was washed three times with water to obtain a catalytically treated insulating core for electroless plating. (2) Plating process 3500g of deionized water was placed in a 5L reactor, and 70g of nickel sulfate as a Ni salt, 5g of sodium acetate and 2g of lactic acid as complexing agents, 0.001g of Pb acetate and 0.001g of sodium thiosulfate as stabilizers, and 1g of PEG-600 as a surfactant were sequentially dissolved to prepare solution (a). The catalyst-treated insulating core was added to the prepared solution (a), and the mixture was dispersed using an ultrasonic homogenizer for 10 minutes. After the dispersion, the pH of the solution was adjusted to 8.0 using ammonia water to prepare solution (b). Solution (c) was prepared by dissolving 300g of deionized water, 33g of DMAB as a reducing agent, and 0.002g of sodium thiosulfate as a stabilizer in a 1L beaker. Solution (d) was prepared by dissolving 500g of deionized water, 155g of nickel sulfate, and 10g of sodium hydroxide in a 1L beaker. While maintaining the temperature of solution (b) in the 5L reactor at 20°C, solution (c) was added using a metering pump at a rate of 5g per minute, and the reactor was heated to 35°C at a heating rate of 0.33°C / min and maintained at that temperature. The pH of solution (b) in the 5 L reactor was adjusted to 8.0 by adding more aqueous ammonia until the solution temperature reached 35°C, and no more aqueous ammonia was added after 75°C. Solution (c) was added, and 5 minutes later, solution (d) was added to the 5L reactor at a rate of 20g per minute using a metering pump. After the addition of solution (c) was completed, the mixture was maintained for 30 minutes to obtain Ni-plated conductive particles. [Examples]
[0061] The solution (d) was prepared in the same manner as in Example 1, except that 3 g of potassium gold cyanide was added to the solution (d). [Reference example]
[0062] Solution (a) was prepared by sequentially dissolving 70g of nickel sulfate as a Ni salt, 5g of sodium acetate and 2g of lactic acid as complexing agents, 0.001g of Pb acetate and 0.001g of sodium thiosulfate as stabilizers, and 1g of PEG-600 as a surfactant in a 5L reactor. The catalyst-treated insulating core was added to the prepared solution (a) and dispersed using an ultrasonic homogenizer for 10 minutes. After dispersion, the pH of the solution was adjusted to 5.5 using ammonia water to prepare solution (b). Solution (c) was prepared by dissolving 500g of deionized water, 280g of sodium hypophosphate as a reducing agent, and 0.002g of sodium thiosulfate as a stabilizer in a 1L beaker. Solution (d) was prepared by dissolving 500g of deionized water, 155g of nickel sulfate, and 5g of sodium hydroxide in a 1L beaker. While maintaining the temperature of solution (b) in the 5L reactor at 65°C, solution (c) was added using a metering pump at a rate of 5g per minute, and the reactor was heated to reach 75°C at a heating rate of 0.33°C and maintained at that temperature. Ammonia water was further added to adjust the pH of solution (b) in the 5 L reactor to 5.5 until the solution temperature reached 75°C, and no more ammonia water was added after 75°C. Solution (c) was added, and 5 minutes later, solution (d) was added to the 5L reactor at a rate of 20g per minute using a metering pump. After the addition of solution (c) was completed and maintained for 30 minutes, conductive particles with a crystalline Ni-P plating layer were obtained. [Examples]
[0063] The preparation was carried out in the same manner as in Example 1, except that solution (d) was prepared by dissolving 500 g of deionized water, 155 g of nickel sulfate, 10 g of hydrochloric acid, and 0.5 g of palladium chloride (PdCl2). <Example of experiment>
[0064] Example 1~ 3. and examples We performed an evaluation of the conductive particles obtained. 1) Measurement of the size of insulating core particles The average diameter of the insulating core particles is determined using the mode value measured with a Particle Size Analyzer (BECKMAN MULTISIZER TM3). The number of conductive particles measured was 75,000. 2)XRD analysis Table 1 summarizes the radii of the 1st to 4th diffraction circles, measured from the diffraction patterns obtained by XRD (X-ray diffraction-SmatLab) analysis using a Cu target in the conductive layer of conductive particles. The radius of the diffraction circle was calculated using Digital Micrograph (ver3.42.3048.0) to determine the four diameters passing through the center of each diffraction circle, as shown in Figure 3. The average of these four diameters was then calculated and divided by 2 to obtain the radius (r). The measurements were taken in the conductive layer at the 1st region adjacent to the insulating core, the 2nd region adjacent to the 1st region, and the 3rd region, the outermost region adjacent to the 2nd region. [Table 1] 3) By grain boundary analysis, the above-mentioned Examples 1- 2. and examples The lengths of the major axes of the grain boundaries were measured, and the results are summarized in Table 2. [Table 2] 4) Measurement of connection resistance (1) Manufacturing of anisotropic conductive film 2g of naphthalene epoxy resin HP4032D (manufactured by DIC, trade name), 20g of phenoxy resin YP-50 (manufactured by Toto Kasei, trade name), 25g of acrylic epoxy resin VR-60 (manufactured by Showa Denko, trade name), 22g of thermosetting agent HXA-3922HP (manufactured by Asahi Chemical, trade name), and 5g of epoxysilane coupling agent A-187 (manufactured by Momentive, trade name) were thoroughly mixed, and a mixture with a solid content of 50% was prepared using toluene as a solvent. After adding the above conductive particles to a weight ratio of 10% of the mixture, an anisotropic conductive paste was prepared by mixing for 5 minutes using a revolving mixer at 400 rpm and rotating at 150 rpm. A 20 μm thick film was made on a release film using the anisotropic conductive paste, and then dried in the air using a hot air drying oven at 75°C for a final thickness of 12 μm to produce an anisotropic conductive film. (2) Electrode for resistance measurement For resistance measurement electrodes, we fabricated a glass substrate with transparent electrodes by depositing ITO (Indium Tin Oxide) onto it, and an FPCB with an electrode width of 20 μm and an electrode spacing of 50 μm. (3) Joining The anisotropic conductive film was cut to a width of 3 mm, and then, using a bonding jig measuring 1 mm in width and 30 mm in length, it was pressed onto a glass substrate containing ITO at 0.2 MPa, 120°C, and 10 seconds. After that, the FPCB was placed on top and bonded at 45 MPa, 200°C, and 20 seconds to fabricate a connecting structure. (4) Measurement of initial connection resistance The resistance was measured using the electrodes of the FPCB in the aforementioned connection structure. The resistance was measured using an ADCMT 6871E Digital Multimeter 2 probe. (5) Measurement of reliability resistance Reliability resistors were measured after being left at 85°C and humidity for 100 hours. To measure the resistance, the connection, which had been left standing for 100 hours, was placed in a 100°C dry oven for 24 hours to remove residual moisture. The resistance was then measured using an ADCMT 6871E Digital Multimeter 2 probe and summarized in Table 3. The criteria for determining the initial connection resistance are as follows: OOO: 2Ω or less OO: More than 2Ω but less than 3Ω O: More than 3Ω and less than 5Ω X: Exceeding 5Ω The criteria for determining the increase in connection resistance after 85°C and 100 hours of reliability are as follows: OOO: Rising resistance below 2Ω OO: Increases when the impedance exceeds 2Ω and falls below 4Ω. O: Increases when exceeding 4Ω and below 6Ω. X: Over-6Ω increase [Table 3]
[0065] The features, structures, and effects exemplified in each of the above-described embodiments can be combined or modified and implemented in other embodiments by a person with ordinary skill in the art to which the embodiments belong. Therefore, the content related to such combinations and modifications should be interpreted as being within the scope of the present invention.
Claims
1. Insulating core and The insulating core includes a conductive layer, The conductive layer is a single layer with no boundaries between regions in a first region adjacent to the insulating core, a second region adjacent to the first region, and a third region located on the outermost side adjacent to the second region. The conductive layer contains at least two elements, In the first, second, and third regions of the conductive layer, at least two diffraction circles are formed in the diffraction pattern analyzed using XRD. Conductive particles, wherein the average length of the long axis of the crystal grains in the entire region of the conductive layer is 8 nm to 13 nm.
2. The conductive particle according to claim 1, wherein the conductive layer comprises Ni and at least one element selected from the group consisting of B, N, Pd, Pt, W, Au, Ag, Mo, and Co.
3. The conductive particle according to claim 1, wherein the radius of the innermost diffraction circle among the diffraction circles is 4.93 (l / nm) ± 0.2 (l / nm).
4. The conductive particle according to claim 1, wherein the conductive layer has elemental content that varies depending on the first region, the second region, and the third region.
5. The conductive particle according to claim 2, wherein the conductive layer comprises at least two elements selected from the group consisting of B, N, Pd, Pt, W, Au, Ag, Mo, and Co.
6. The conductive particle according to any one of claims 1 to 5, further comprising an insulating layer or insulating particles on the surface of the conductive layer.
7. The conductive particle according to any one of claims 1 to 5, wherein the outermost layer on the conductive layer is treated with a hydrophobic rust inhibitor for rust prevention.
8. An anisotropic conductive material comprising conductive particles according to any one of claims 1 to 7.
9. A connecting structure comprising conductive particles according to any one of claims 1 to 7.
10. An electronic device comprising conductive particles according to any one of claims 1 to 7.
Citation Information
Patent Citations
Electroconductive particle, electroconductive material, and connection structure
JP2021027027A
Conductive particles, conducting material, and connection structure
WO2015037711A1